2004
DOI: 10.1074/jbc.m401206200
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of Amino Acid Sequence Features of a- and c-Subunits of ATP Synthases of Alkaliphilic Bacillus with the Bacillus Consensus Sequence Results in Defective Oxidative Phosphorylation and Non-fermentative Growth at pH 10.5

Abstract: Here we show that these properties, in alkaliphilic Bacillus pseudofirmus OF4, depend upon alkaliphile-specific features in the proton pathway through the a-and c-subunits of ATP synthase. Site-directed changes were made in six such features to the corresponding sequence in Bacillus megaterium, which reflects the consensus sequence for non-alkaliphilic Bacillus. Five of the six single mutants assembled an active ATPase/ATP synthase, and four of these mutants exhibited a specific defect in non-fermentative grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
101
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(108 citation statements)
references
References 63 publications
(56 reference statements)
5
101
1
1
Order By: Relevance
“…This will make it possible to test whether one or more of the alkaliphile-specific features of the ATP synthase and cytochrome caa 3 facilitate the interactions observed here and/or apparent proton sequestration in bioenergetic experiments. A candidate in the alkaliphile ATP synthase would be the unusually polar loop on the external side of the a-subunit, near the putative proton uptake pathway, that was shown to be required for optimal OXPHOS at high pH but not critically involved in the proton-gating function (15). A candidate of interest in the cytochrome caa 3 is the unusually acidic patch that was noted when the operon encoding the complex was first cloned and sequenced (17).…”
Section: Stepr Studies Of Spin-labeled Cytochrome Caa 3 Embedded In Pmentioning
confidence: 99%
See 2 more Smart Citations
“…This will make it possible to test whether one or more of the alkaliphile-specific features of the ATP synthase and cytochrome caa 3 facilitate the interactions observed here and/or apparent proton sequestration in bioenergetic experiments. A candidate in the alkaliphile ATP synthase would be the unusually polar loop on the external side of the a-subunit, near the putative proton uptake pathway, that was shown to be required for optimal OXPHOS at high pH but not critically involved in the proton-gating function (15). A candidate of interest in the cytochrome caa 3 is the unusually acidic patch that was noted when the operon encoding the complex was first cloned and sequenced (17).…”
Section: Stepr Studies Of Spin-labeled Cytochrome Caa 3 Embedded In Pmentioning
confidence: 99%
“…This property reflects a blockage of proton flux both to and from the bulk phase at pH ≥ 9.5 that protects against cytoplasmic alkalinization during sudden exposure to high pH. Two residues of the F 0 -ATP synthase asubunit have been shown to participate in this pH-dependent proton "gating", one of which is also required for ATP synthesis at high pH (15). These findings led us to propose that a kinetically sequestered proton path from the respiratory chain to the ATP synthase at high pH is supported by properties of the participating complexes as well as the membrane and may involve dynamic protein-protein interactions between the ATP synthase and one of the terminal oxidases of the respiratory chain, the proton-pumping caa 3 oxidase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). Mutagenesis studies of Lys-180 of B. pseudofirmus OF4 showed that its mutation to the consensus glycine of non-alkaliphiles resulted in a major deficit in ATP synthesis at pH 10.5, while significant capacity for ATP synthesis was retained at near neutral pH (37). We hypothesized that, at high pH, Lys-180 is a participant of the proton uptake path that is required for capture of entering protons and passage of the protons to the interface of the c-ring with the a-subunit.…”
mentioning
confidence: 99%
“…B. pseudofirmus OF4 and other alkaliphilic Bacillus species share sequence motifs in the a-and c-subunits of their proton-coupled ATP synthases (30,33,35). Initial mutagenesis work showed that several of these sequence deviations from the neutralophilic Bacillus consensus have indispensible roles in the synthetic function of the enzyme and non-fermentative growth on malate at high pH, but are not required for hydrolytic ATPase activity or non-fermentative growth of B. pseudofirmus OF4 near neutral pH (36,37). Recent structural studies on the B. pseudofirmus OF4 tri-decameric c-rotor have begun to provide insights into how the major motifs of the alkaliphile c-subunits impact the structure and support the function of the rotor at high pH (31).…”
mentioning
confidence: 99%